Ambiente percebido, suporte social e atividade fisica em adultos : um estudo de base populacional. - Amorim, Tales Emílio Costa (2008)
Background: Most of the data on the association between physical activity and the environment are derived from high-income countries. The aim of this study was to evaluate the association between the perceived environment and physical activity (leisure-time and transport-related) in a population-based sample. Methods: Cross-sectional study including 972 adults (20-69 years) living in the urban area of Pelotas, Brazil. Physical activity was measured using the long International Physical Activity Questionnaire. Environmental variables were assessed using a modified version of the Neighborhood Environment Walkability Scale. Results: 69.8% (95%CI; 66.9-72.7) and 51.9% (95%CI; 48.8-55.1) of the subjects did not reach 150 min/wk of leisure-time physical activity and active transportation, respectively. While leisure-time physical activity increased with increasing socioeconomic level, the opposite was observed for transport-related activity levels. Subjects living close to green areas were more likely to be active in leisure-time, as well as those who reported to live in safe neighborhoods. Transport-related physical activity was higher among individuals living in areas with garbage accumulation, and was lower among those who live in neighborhoods which are difficult to walk or cycle due to traffic. Social support was strongly associated with leisure-time physical activity. Conclusion: Safety investments, which are urgently required in Brazil, are likely to have a desirable side effect at increasing physical activity at the population level. Also, building enjoyable and safe public spaces for physical activity practice must be prioritized, so that social networks can be constructed or enhanced, making active lifestyles a rule, and not an exception in Brazil.